Enhanced Growth and Ethanol Oxidation by Overexpressed caiA Gene Encoding acyl-CoA Dehydrogenase in Komagataeibacter medellinensis NBRC 3288 - Phisurang Konjanda (Science Faculty of Chiang Mai University, 2019)
In this study, the caiA gene encoding acyl-CoA dehydrogenase (ACAD) from thermotolerant Komagataeibacter intermedius MSKU 9 was cloned and characterized. Two specific primers for amplification of an entire caiA gene were designed from a draft genome sequence of K. intermedius MSKU 9 (MSKU 9_0337 homolog). Sequencing analysis of the 1.2 kb PCR product revealed possible open reading frame (ORF) of 1,182 bp with a start codon ATG at the 1,001st - 1,003rd position and a stop codon TAA at the 2,183th - 2,185th position. The deduced amino acid sequences of the caiA gene had 393 residues. The overexpression of the caiA gene in a non-thermotolerant strain, K. medellinensis NBRC 3288, was investigated. K. medellinensis NBRC 3288 harboring pMVcaiA showed a better growth rate than that observed in the parental strain at 33°C and was more tolerant to both ethanol at 30°C and acetic acid even at 37°C. Thus, it can be suggested that the caiA gene influenced and improved growth, acetic acid tolerance and ethanol oxidation in acetic acid bacteria at high temperature.